Impact of a Food Sanitation Literacy Program on Food Handlers’ Behavior: A Quasi-Experimental Evaluation in the Upper Tapi Basin, Thailand - Pimpenjun Pan-in; Pimpiengjun Pan-in; Somsiri Decharat (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: The upper Tapi River area has been developed into a tourist attraction with more accommodations and restaurants. Food sanitation surveillance is therefore necessary to reduce the risk of foodborne diseases. This study addresses the need to evaluate the effectiveness of a Food Sanitation Literacy Development Program (FSLDP) on food handlers’ behavior. Methods: This research is quasi-experimental with a one-group pretest-posttest design to study the effect of the food sanitation literacy development program (FSLDP) on the behavior of food handlers. A sample of entrepreneurs at 135 food and beverage restaurants will be obtained between May and October 2024. The Food Sanitation Literacy Development Program (FSLDP) was used in the experimental group for a total of 4 weeks, which consisted of organizing group activities with activities to enhance food sanitation knowledge, lectures, discussions, playing games, and practicing. Results: Results showed a significant increase in food sanitation literacy, with mean scores rising from 99.89 (SD = 17.75) before the program to 125.38 (SD = 17.12) immediately after, and further to 126.82 (SD = 19.88) at the one-month follow-up. All six dimensions—access to information, knowledge and understanding, communication skills, self-management, media literacy, and decision-making—demonstrated consistent and sustained improvements. Food sanitation behavior scores similarly increased from 46.74 (SD = 9.20) at baseline to 62.50 (SD = 7.80) immediately post-program and 64.50 (SD = 5.85) at one month, indicating both immediate and maintained behavioral gains. Personal hygiene behaviors, particularly handwashing habits and correct handwashing steps, improved significantly, whereas appearance when handling food and behavior during work showed minimal change. Repeated-measures ANOVA confirmed that these improvements were statistically significant (p < 0.001) and largely maintained over time. Conclusion: These findings suggest that structured educational interventions, supported by practical exercises and access to digital resources, can effectively enhance food safety literacy, foster proper hygiene practices, and contribute to the long-term implementation of safe food handling behaviors among food handlers in tourism-intensive areas.